PERBEDAAN JUMLAH LEUKOSIT CAIRAN SULKUS GINGIVA ANTARA VEGETARIAN MURNI DAN VEGETARIAN TIDAK MURNI: Kajian pada Mahasiswa di Yogyakarta - , RAHMA ARIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vegetarian is a person who lives from consuming vegetable products with or without milk and eggs, but avoid the consumption of meat, poultry and seafood. Vegetarians who eat only plant-based foods are called vegans or pure vegetarians, while vegetarians who eat plant foods, milk, eggs and dairy products are called impure vegetarian. Nutritional imbalances indirectly influencing the durability of periodontal tissues. The condition of the periodontal tissues is closely related to the work of leukocytes in the body's defense mechanism. This study aimed to determine differences leukocyte count in the gingival crevicular fluid between pure vegetarians and impure vegetarians (in collage student of Yogyakarta). This research was an observational analytic with cross-sectional approach. Performed at 15 pure vegetarian and 15 impure vegetarian people aged 17-30 years old who had been on a diet at least 2 years and live in Yogyakarta. Sampling was done by taking the gingival crevicular fluid from one of lower anterior teeth on labial surface of gingival that clinically normal. Gingival crevicular fluid was diluted with aquades sterile and put in Neubeur Improved Chamber, and then leukocyte counts performed under a light microscope with weak magnification (10x). Data on the number of leukocytes was analyzed using independent t test. The results showed there were differences leukocyte counts in the gingival crevicular fluid were significantly (p <0.05) between pure vegetarians and impure vegetarians (in collage student of Yogyakarta). It was concluded that leukocyte count in gingival crevicular fluid on pure vegetarians was higher impure vegetarians. Keywords: Impure vegetarians, Leukocyte, Pure Vegetarians